2002
DOI: 10.1093/clinchem/48.10.1689
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of an ELISA for Human Trefoil Factor 3

Abstract: Background: The three trefoil factors (TFF1, TFF2, and TFF3) are small peptides believed to cross-link mucous glycoproteins and to play a role in the maintenance and repair of the gastrointestinal mucosa. To define the physiologic and potential diagnostic values of TFF3, assays able to measure TFF3 are warranted. Methods: An ELISA was developed that uses two antibodies from rabbits immunized with recombinant human TFF3 and a calibrator (3–100 pmol/L) prepared from recombinant human TFF3. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 26 publications
2
30
1
Order By: Relevance
“…The results for the control group were in accord with our previously published works . TFF1 was the most abundant of the peptides in serum.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The results for the control group were in accord with our previously published works . TFF1 was the most abundant of the peptides in serum.…”
Section: Resultssupporting
confidence: 91%
“…We found that subjects with COPD had highly significant increases in both sputum levels and serum levels of TFF1 and TFF3 and increased level of TFF2 in serum. Compared with similar investigations related to diseases in the GI tract, in which serum TFF levels in diseased groups increased by less than 50% , the increases in the COPD group were substantially higher both in serum and in sputum. No changes in TFFs were detected in the group of patients with asthma.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Extractions were kept at À80°C until analysis. The TFF1, TFF2, and TFF3 concentrations were assessed on the 1:100 extractions after a further 100-fold dilution employing in-house enzyme-linked immunosorbent assay methods (19,20). Furthermore, hemoglobin concentrations in the extracts were determined using the routine method of the laboratory (Cobas6000, Roche A/S Hvidovre, Copenhagen, Denmark; http://www.roche.dk/home/produkter.html).…”
Section: Methodsmentioning
confidence: 99%
“…The Trefoil factor peptides (TFFs) constitute a family of small (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) kDa) molecules containing one (TFF1 and TFF3) or two (TFF2) trefoil domains (7). TFFs are most abundantly expressed in the gastrointestinal tract, yet they can be detected in virtually all tissues containing mucin-secreting cells including the endocervix and the uterus (7,8).…”
Section: Key Messagementioning
confidence: 99%